Iconic method in reading inferences skills in eight and nine year old schoolchildren of a state educational institution of the Constitutional Province of Callao - Holguin Alvarez, Jhon Alexander (2017)
The study was conducted in a State Educational Institution of the Constitutional Province of Callao, Peru. Type pre experimental with one group pre and posttest, aimed to determine the improvement of Inferential Reading Skills - HIL, through the design and implementation of a program of Iconic method based on experimental evidence in the study of understanding and learning (Estaún, 1998; Monge, 1992; Rengifo and Marulanda, 2007), in a sample of 93 students averaging between eight and nine years old. An instrument being elaborated based on the theories of Goodman (2002) and Inga (2009); to measure these skills. The implementation of the program was more effective in the ability to solve problems.